CURRENT METHODS OF TRAINING FOR DENTAL TECHNICIANS - Magda-Ecaterina Antohe; Monica Andronache; Ramona Diana Feier; Ovidiu Stamatin; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2018)
Aesthetics and functionality are two outstanding parameters of great importance with the clinical purpose of both fixed and mobile restorations.Our study aims to individualize the methods of training dental technicians for optimal insertion into the labor market.Material and method:The current lucrative methods are represented by the realization of wax-ups, mounted in articulators, thus defining the final therapeutical solutions, with the individualization of the restorative stages corroborated with the specific preparations.Results and discussions:The realization of wax-ups in the complex oral rehabilitation is a particularly important stage in the training of dental technicians, perfecting their practical skills, and especially individualizing the therapeutic solutions on each clinical case. Another important aspect of the training methods of dental technicians is the deepening of analog-digital binomial both in fixed prostheses and in mobilizable prostheses. Conclusions:The importance of the formative aspects towards the performance in the context of the oral rehabilitation of the various clinical situations in the dental technical studies is an essential condition for connecting the future dental technicians to the prosthetic building standards required by the current society.